Research on mechanism and practice of expansion‐induced fracturing and pressure relief in deep coal mines - Shitan Gu; Zhiyao Liu; Wenshuai Li; Bangyou Jiang; Changpeng Chen (Energy Science & Engineering)
Abstract A nonexplosive expansion method is proposed to apply in the field of rock burst prevention and control in coal mine. The principle of the expansive agent reaction was analysed and specimens with one hole and two holes were tested with and without axial stress or an expansive agent. The results showed that the reaction products of the expansive agent exhibited excellent fluidity and did not induce secondary stress concentration within the specimens. The specimens with two holes exhibited more severe and intricate fractures upon introduction of the expansive agent, and the formation of crisscross networks of cracks occurred in both the horizontal and vertical directions. Stress concentration became more pronounced as the distance between the two holes decreased, making the specimen more vulnerable to cracking. A field test was conducted to evaluate the effectiveness of pressure relief through expansion‐induced fracturing in the roadway of 1318 working face. The results from the field test demonstrated that the quantity of coal powder in the deep area significantly decreased after expansion‐induced fracturing and fell well below the early warning index of the drilling cutting method.